Creating Monumental Tombs of Cyprian Salamis: The Role of the Funeral Rites, the Prototypes and Parallels - Nalimova, Nadezhda A.; Savina, Irina S. (Actual Problems of Theory and History of Art, 2019)
This article discusses the architecture of the Royal Necropolis at Iron Age Salamis (Cyprus). In search of possible prototypes and parallels to the Salamis tombs, the authors analyze a wide range of funerary monuments including those discovered in Cyprus in recent decades. The specific features of funeral architecture are considered in the context of the formation, existence, and interaction of the Cypriot city-kingdoms. The complicated political and ethno-cultural situation in the region is taken into account as well. It seems probable that creating a kind of universal aristocratic tomb-type, Salaminian elite and builders involved in the process took as a starting point the elements of Mycenaean culture adopted throughout the long history of contacts with the Aegean. The local traditions, contacts with Asia Minor and Levant also played their role. Nevertheless, the rite itself, which has if not the origin then parallels in the Aegean world, seems to be crucial. It determines the parameters, forms and principles of planning decisions.
Keywords: funerary architecture; dromos; horse sacrifices; ekphora; Salamis; ancient Cyprus; Royal necropolis; funerary ritual